Raum-Zeit des Terrors - Struktur und Inszenierung des Terrorismus und seine Darstellungen im Film - Weitze, Almut (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2011)
This thesis investigates whether terrorism has a filmic form or structure and if this cinematic structure corresponds to the staging and production of terrorism. Furthermore, it explores the extent to which the cinematographic devices, the mise-en-scene, the editing, and the montage found in the filmic images parallel different forms of terrorism, such as the terrorism of the IRA, the RAF, and al-Qaida, and if the filmic representations differ according to these specific terrorist organizations.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin.